2016
DOI: 10.1016/j.ajhg.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals

Abstract: Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 78 publications
4
99
0
Order By: Relevance
“…Our meta-analyses confirmed two known independent ANK1 variants associated with MCHC: an intronic SNP (rs4737009, MAF ¼ 19.8%, p ¼ 1.3 3 10 À8 ) and a low-frequency missense variant (rs34664882, p.Ala1462Val, MAF ¼ 2.9%, p ¼ 1.7 3 10 À16 ) (Table S5; N.P., U.M.S., J.B.-J., and M.-H.C., unpublished data). 17 In the accompanying BCX PLT article, 20 we report that the same MAP1A rs55707100 allele (p.Pro2349Leu [c.7046C>T]) associated here with decreased HGB concentration is also associated with increased PLT count. Furthermore, recent studies have identified associations between rs55707100 and HDL-cholesterol and triglyceride levels (S. Mukherjee, 2015, ASHG, conference).…”
Section: Prioritization Of Candidate Genes and Genetic Variantsmentioning
confidence: 88%
See 2 more Smart Citations
“…Our meta-analyses confirmed two known independent ANK1 variants associated with MCHC: an intronic SNP (rs4737009, MAF ¼ 19.8%, p ¼ 1.3 3 10 À8 ) and a low-frequency missense variant (rs34664882, p.Ala1462Val, MAF ¼ 2.9%, p ¼ 1.7 3 10 À16 ) (Table S5; N.P., U.M.S., J.B.-J., and M.-H.C., unpublished data). 17 In the accompanying BCX PLT article, 20 we report that the same MAP1A rs55707100 allele (p.Pro2349Leu [c.7046C>T]) associated here with decreased HGB concentration is also associated with increased PLT count. Furthermore, recent studies have identified associations between rs55707100 and HDL-cholesterol and triglyceride levels (S. Mukherjee, 2015, ASHG, conference).…”
Section: Prioritization Of Candidate Genes and Genetic Variantsmentioning
confidence: 88%
“…BCX is interested in the genetics of all main hematological measures and is divided into three main working groups: RBC, white blood cell (WBC), 21 and platelet (PLT). 20 For the RBC working group, we analyzed seven traits available in up to 130,273 individuals: RBC count (310 12 /L), HGB (g/dL), HCT (%), MCV (fL), MCH (pg), MCHC (g/dL), and RDW (%) ( Table S2). The BCX procedures were in accordance with the institutional and national ethical standards of the responsible committees and proper informed consent was obtained.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, to assess whether the WBC variants were associated with other blood cell traits, we obtained effect sizes and p values for these variants from RBC-and platelet-related traits exome array analyses within the BCX consortium. 32,33 …”
Section: Phenome-wide Association Study Analysismentioning
confidence: 98%
“…demonstrated association of rare variants in BAK1, MPL, ITGB3, CD109 , and CD36 with platelet count and MPV, which led to the development of the Exomechip, a quick genotyping method enriched in rare coding variants demonstrated in previous WES studies and common SNP variants identified in GWAS studies. The ability to increase sample size enabled the Exomechip technology to identify novel gene associations, including JAK2 , TUBB1 , MAP1A , ZMIZ2 , PEAR1 , and PACSIN2 34, 35…”
Section: Genomics Approaches To Platelet Traitsmentioning
confidence: 99%